Reflections and Strategies for Full-cycle Stroke Rehabilitation - JIA Jie (Zhongguo quanke yixue, 2025)
Post-stroke patients are often left with different degrees of functional impairment, and in the process of returning from the medical institution to the community and home, it is necessary for medical institutions at all levels to cooperate and interact, so as to form a good full-cycle rehabilitation closed loop. At present, the application of full-cycle stroke rehabilitation is progressing, but some resistance still exists. This articel is based on the concept of full-cycle rehabilitation for stroke, combined with the current situation of the development of community-based rehabilitation, we also think about the development of the full-cycle rehabilitation and community-based rehabilitation link for stroke. The article emphasizes the importance of "community-based inflection-point rehabilitation" and the need to establish standards of community-based rehabilitation. Moreover, the article also mentions the need to emphasize the full-cycle stage of rehabilitation for stroke patients, explore the development strategy of community-based rehabilitation, and effectively improve the quality of life in community and family.